2010
DOI: 10.1002/elps.200900646
|View full text |Cite
|
Sign up to set email alerts
|

CE‐LIF‐MSn profiling of oligosaccharides in human milk and feces of breast‐fed babies

Abstract: Mixtures of the complex human milk oligosaccharides (HMOs) are difficult to analyze and gastrointestinal bioconversion products of HMOs may complicate analysis even more. Their analysis, therefore, requires the combination of a sensitive and high-resolution separation technique with a mass identification tool. This study introduces for the first time the hyphenation of CE with an electrospray mass spectrometer, capable to perform multiple MS analysis (ESI-MS(n)) for the separation and characterization of HMOs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 49 publications
2
69
0
Order By: Relevance
“…In addition, Gal(b1 -4)GlcNAc(b1 -6)Gal(b1 -4)Glc (type II) and Gal(b1 -4)[Fuc(a1 -3)]GlcNAc(b1 -6)Gal(b1 -4)Glc (type II) were found in the faeces, although these are not present in human milk (Albrecht et al, 2010). These results suggest that LNT is preferentially digested and that LNB, released from Gal(b1 -3)GlcNAc(b1 -3)[Gal(b1 -4)GlcNAc(b1 -6)]Gal(b1 -4)Glc (LNH) or Gal(b1 -3)GlcNAc(b1 -3){Gal(b1 -4)[Fuc(a1 -3)]GlcNAc(b1 -6)}Gal(b1 -4)Glc (monofucosyl LNH) by the action of lacto-N-biosidase, is utilized by bifidobacteria during the passage of HMO through the gastrointestinal tract when the infant consumes breast milk, so that the above type II saccharides remain in the faeces.…”
Section: Evolution Of Milk Oligosaccharides and Lactosementioning
confidence: 99%
“…In addition, Gal(b1 -4)GlcNAc(b1 -6)Gal(b1 -4)Glc (type II) and Gal(b1 -4)[Fuc(a1 -3)]GlcNAc(b1 -6)Gal(b1 -4)Glc (type II) were found in the faeces, although these are not present in human milk (Albrecht et al, 2010). These results suggest that LNT is preferentially digested and that LNB, released from Gal(b1 -3)GlcNAc(b1 -3)[Gal(b1 -4)GlcNAc(b1 -6)]Gal(b1 -4)Glc (LNH) or Gal(b1 -3)GlcNAc(b1 -3){Gal(b1 -4)[Fuc(a1 -3)]GlcNAc(b1 -6)}Gal(b1 -4)Glc (monofucosyl LNH) by the action of lacto-N-biosidase, is utilized by bifidobacteria during the passage of HMO through the gastrointestinal tract when the infant consumes breast milk, so that the above type II saccharides remain in the faeces.…”
Section: Evolution Of Milk Oligosaccharides and Lactosementioning
confidence: 99%
“…We hypothesize that LNB released from type I in preference of type II HMOs by Bifidobacterium bifidum lacto-N-biosidase are utilized by multple strains of colonic bifidobacteria in breast-fed infants, leading to their predominance. Albrecht et al [42] compared oligosaccharides in human milk and in feces of breast-fed babies by capillary electrophoresis with a laser induced fluorescence detector coupled to a mass spectrometer (CE-LIF-MS n ). They found that the relative level of LNT (type I) was markedly lower in the fecal extract than in breast milk, while the relative level of LNnT (type II) was higher in the feces.…”
Section: Type Of Oligosaccharidementioning
confidence: 99%
“…CE with laser-induced fluorescence coupled to mass spectrometry (CE-LIF-MS) is effective for derivatized HMO. Labeling with 8-aminopyrene-1,3,6-trisulfonic acid (APTS) introduces a fluorophore for the LIF detection, while simultaneously adding negative charge needed for the separation (49)(50)(51). However although good separation can be achieved using offline CE-LIF using very fast runs (around 9 minutes), both resolution and separation time have to be compromised when coupling CE to mass spectrometry (52).…”
Section: Compound Profiling Of Hmosmentioning
confidence: 99%